Healthy Diet and Nutrition Education Program among Women of Reproductive Age: a Necessity of Multilevel Strategies or Community Responsibility - Yashvee Dunneram; Rajesh Jeewon (Tabriz University of Medical Sciences, 2015)
Background: Reproductive years represent a major proportion of women‟s life. This review focuses on recommended nutritional considerations, physical activity pattern as well as the effect of nutrition education (NE) on behavior modification and health outcomes of women of reproductive age using either single-level, multiple-level or community-level interventions. Methods: For this narrative review, numerous searches were conducted on databases of PubMed, Science Direct and Google Scholar search engine using the keywords women, reproductive age, NE, interventions, community-based. Results: Even though single intervention is effective, multiple intervention programmes in addition to behavior modification components are even more successful in terms of modified behaviors and health outcomes. Moreover, community based interventions using multilevel strategies are further useful for improved health outcomes and behavior modification. Conclusion: NE programmes have been effective in positive behavior modifi-cation measured in terms of eating pattern and health quality. Thus, it is recommended that health professionals use multiple intervention strategies at community level to ensure improved outcomes. Political support is also required to create culturally sensitive methods of delivering nutritional programmes. Finally, as policy is dependent on program cost, nutritional programmes need to combine methods of cost analysis to show cost effectiveness of supplying adequate nutrition for women throughout the lifecycle.